Climate change effects on the thermal stratification of Lake Diefenbaker, a large multi-purpose reservoir. Issue 1 (3rd April 2021) - Morales-Marin, L. A.; Carr, M.; Sadeghian, A.; Lindenschmidt, K. E.
Abstract: Large multi-purpose reservoirs serve not only to generate hydropower but to supply water for agricultural irrigation, animal and human consumption and to provide flood control. One of the key factors affecting physical functioning and deteriorating aquatic ecosystems in reservoirs is climate change. For instance, increases in water temperature accelerate chemical reaction rates, decomposition rates and oxygen demand at the water-sediment interface. Earlier thermal stratification onset, and longer and more intense reservoir thermal stratification are all consequences of global warming. Such disruptions in thermal stratification have been associated with reductions in hypolimnion dissolved oxygen, increasing anoxia events and enhancing reservoir eutrophication. In this research paper, we implement the 2 D hydrodynamics and water quality model, CE-QUAL-W2, to investigate the effects of climate change and streamflow scenarios on the thermal structure of Lake Diefenbaker, a large, multipurpose reservoir, located in Saskatchewan, Canada. Model results indicate that meteorological variability will dictate a nonlinear increase in reservoir water temperature in the coming decades, where larger increases in water temperature will occur during summer and fall in the upper layers. Also, decreases in reservoir streamflows will reduce water temperature at intermediate layers during summer and fall. Our model can be used as a tool to mitigate and manage the effects of climate change on the reservoir water quality.